Natural Concentrations of Iodine in Common Salts Produced from Popular Lagoons in Ghana and their Potential to Eliminate Iodine Deficiency Disorders - Benjamin, Bartels; Addo, Vanderpuye Andreas Nii; Yao, Gadzekpo Victor Patrick (International Journal of Environment, Agriculture and Biotechnology, 2023)
Background and objectives: Iodine deficiency is a global public health concern. This deficiency if not cured results in illness like goiter, cretinism and reduced intelligence quotient that disrupts normal physical and mental functions. The USI programme was introduced to improve household’s iodine intake, in Ghana the mandatory salt iodisation law that specifies that all salts meant for consumption must be iodised has been long passed to give credence to the USI. Yet, some Ghanaian families are still deliberately or ignorantly consuming salt containing less or no iodine at all with the perception that common salt naturally contains enough iodine. Hence, this study assesses the levels of iodine in salts from popular lagoons, which are major salt producing centres in Ghana. Methods: Two hundred (200) samples of salts were collected in six (6) months from popular major salt producing lagoons, namely, Ada-Songhor, Nyanyano, Keta, Amisa and Benya lagoons. In addition, five (5) brands of packaged refined salts also sampled for their iodine for comparative analyses. Questionnaire was administered to household’s women in charge of meal preparation to solicit information about preference for salt and knowledge about IDD. Statistical Package for Social Sciences (SPSS) version 16 and Microsoft Excel were used in data analysis. Results: The lagoon salt samples did not record any measurable iodine (0 ppm). Ninety-three percent of respondents were ignorant about benefits of iodised salt, whilst 50.4% prefer non-iodised salt. Conclusion: The ignorance about the absence of iodine in crude salt could influence the extent of the ignorance about benefits of iodine and preference for non - iodised salt.